OUTCOME OF OPERATIVE TREATMENT OF ACETABULAR FRACTURES: SHORT TERM FOLLOW-UP - Qadir, Raja Irfan; Bukhari, Syed Imran (Journal of Ayub Medical College Abbottabad, 2015)
Background: Fractures of the acetabulum result from high energy accidents. The anatomic location of the acetabulum, as well as the three-dimensional structure of the bone, makes the treatment of these injuries extremely challenging. The objective of this study was to determine the outcome of operative treatment of acetabulum fractures with one year follow-up. Methods: In this descriptive case series, 31 patients with acetabular fracture were admitted in North West General Hospital, Peshawar, from July 2010 to Sept 2013. Patients were followed-up till one year. In follow-up, patients were assessed clinically with Merle d' Aubigne and Postel grading method. Radiological assessment was done using Matta criteria. Results: All patients were male. Twelve (38.7 %) were managed non-operatively, as they fulfilled criteria for non-operative treatment and 19 (61.3%) patients were operated after fulfilling the criteria for internal fixation; they were included for analysis. Ages ranged from 20-60 years with mean age of 37.21±10.07 years. Fourteen (73.7%) patients had anatomic reduction and 5 (26.3 %) patients had imperfect reduction based on Matta radiographic criteria. At 1 year follow-up, we had 16 (84.2 %) excellent hips, 2 (10.5%) good hips and 1 (5.3%) poor hip , based on radiographs; and clinically we had 9 (47.4 %) hips with excellent function, 7 (36.8 %) hips with good outcome, 2 (10.5 %) had fair function and 1 (5.3 %) patient had poor function. Conclusion: Our results show that internal fixation of acetabular fractures lead to good outcome in majority of patients. Keywords: Acetabular fractures, anatomic reduction, imperfect reduction